Kontruksi Sosial Tradisi Sekaten Surakarta Dalam Perspektif Teori Tafsir Sosial - Mochammad Fiki Eko; Dhiyaul Haqqi Al-Mumtaza; Yoga Parulian Panggabean (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Sekaten is an annual event held by Surakarta Palace in Solo area to commemorate the birthday of Prophet Muhammad SAW. When the condition of the society was still traditional, Sekaten tradition was used as a medium of proselytization for scholars and sultans to spread and teach Islamic values. Over time, entering the modern era has caused a cultural shift in which the Sekaten tradition is used as a tourism icon. The acceptance of Sekaten culture by the community includes the externalization stage where each individual will try and learn and interpret what is outside himself. Then it continues to the objectivation stage with the existence of social reality created by humans, of course, it will be seen as something that has meaning and it will affect certain communities. And in the end, the community enters the internalization stage where the individuals involved will absorb the values, norms, and roles that exist in it, so that the social structure forms subjective awareness.